Gendered paradoxes : women's movements, state restructuring, and global development in Ecuador - Lind, Amy (Book collections on Project MUSE., 2005)
Since the early 1980s, Ecuador has experienced a series of events unparalleled in its history. Its "free market" strategies exacerbated the debt crisis, and in response new forms of social movement organizing arose among the country's poor, including women's groups. Gendered Paradoxes focuses on women's participation in the political and economic restructuring process of the past twenty-five years, showing how in their daily struggle for survival Ecuadorian women have both reinforced and embraced the neoliberal model yet also challenged its exclusionary nature. Drawing on her extensive ethnographic fieldwork and employing an approach combining political economy and cultural politics, Amy Lind charts the growth of several strands of women's activism and identifies how they have helped redefine, often in contradictory ways, the real and imagined boundaries of neoliberal development discourse and practice. In her analysis of this ambivalent and "unfinished" cultural project of modernity in the Andes, she examines state policies and their effects on women of various social sectors; women's community development initiatives and responses to the debt crisis; and the roles played by feminist "issue networks" in reshaping national and international policy agendas in Ecuador and in developing a transnationally influenced, locally based feminist movement.